The Antioxidant Properties of Pectin Fractions Isolated from Vegetables Using a Simulated Gastric Fluid - Vasily V. Smirnov; Victoria V. Golovchenko; Fedor V. Vityazev; Olga A. Patova; Nikolay Yu. Selivanov; Olga G. Selivanova; Sergey V. Popov (Journal of Chemistry)
The antioxidant properties of vegetable pectin fractions against intraluminal reactive oxygen species were elucidated in vitro in conjunction with their structural features. The pectin fractions were isolated using a simulated gastric fluid (pH 1.5, pepsin 0.5 g/L, 37°C, 4 h) from fresh white cabbage, carrot, onion, and sweet pepper. The fraction from onion was found to inhibit the production of superoxide radicals by inhibiting the xanthine oxidase. The high molecular weight of onion pectin and a large number of galactose residues in its side chains appeared to participate in interaction with xanthine oxidase. All the isolated pectic polysaccharides were found to be associated with protein (2–9%) and phenolics (0.5–0.7%) as contaminants; these contaminants were shown to be responsible for the antioxidant effect of vegetable pectin fractions against the hydroxyl and 1,1-diphenyl-2-picrylhydrazyl radicals.